2018
DOI: 10.1155/2018/8258246
|View full text |Cite
|
Sign up to set email alerts
|

Shenqi Fuzheng Injection Reverses Cisplatin Resistance through Mitofusin‐2‐Mediated Cell Cycle Arrest and Apoptosis in A549/DDP Cells

Abstract: The goal of this evaluation was to examine the mechanisms of Shenqi Fuzheng injection (SFI), an extract made from the plants Radix Astragali and Radix Codonopsis, in the process of chemotherapy sensitivity in non-small-cell lung cancer (NSCLC) cells. We investigated the expression of mitofusin-2 (Mfn2), a mitochondrial GTPase that may be related to chemoresistance, and found that Mfn2 expression was lower in human cisplatin-resistant lung carcinoma A549/DDP cells than in cisplatin-susceptible A549 cells. Chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 46 publications
2
16
0
1
Order By: Relevance
“…Here, we selected PC-9/GR, H1975 and H1650 cells to detect synergistic effects of SFI and gefitinib. Results suggested that SFI combined with gefitinib to inhibit cell proliferation, clonogenicity and induce apoptosis, which were consistant with the study conducted by Xiong Y, et al They documented that SFI increased chemotherapy sensitivity in cisplatin resistance of NSCLC cells through regulating cell cycle and initiating mitochondrial apoptosis 37. We further validated the underlying mechanism of SFI reversing gefitinib resistance was the inhibition of MAPK/SREBP1 pathway.…”
Section: Discussionsupporting
confidence: 85%
“…Here, we selected PC-9/GR, H1975 and H1650 cells to detect synergistic effects of SFI and gefitinib. Results suggested that SFI combined with gefitinib to inhibit cell proliferation, clonogenicity and induce apoptosis, which were consistant with the study conducted by Xiong Y, et al They documented that SFI increased chemotherapy sensitivity in cisplatin resistance of NSCLC cells through regulating cell cycle and initiating mitochondrial apoptosis 37. We further validated the underlying mechanism of SFI reversing gefitinib resistance was the inhibition of MAPK/SREBP1 pathway.…”
Section: Discussionsupporting
confidence: 85%
“…[11]. Shenqi Fuzheng Injection also contained this ingredient and possessed growth inhibitory effect toward lung cancer cell line [12,13]. Several lines of evidence indicated that this compound was used to treat cardiovascular disease, rheumatism, and hemorrhage [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous study also reported that SFI could re-sensitized chemotherapy to tumour cells through the initiation of mitochondrial apoptosis (Xiong et al. 2018). Based on the results of this meta-analysis, SFI could be recommended as complementary treatment for breast cancer patients.…”
Section: Discussionmentioning
confidence: 86%